Perubahan Perilaku Sosial Masyarakat Dalam Penertiban Pelanggaran Parkir Di Badan Jalan - Ni Luh Tut Tri Ratnawati; Nyoman Sri Subawa (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2021)
The phenomenon of illegal parking on the road bodies of Denpasar City is often encountered. The need for parking space tends to increase, the problem of urban phenomena often occurs such as traffic jams and the number of buildings or places where businesses are built do not have adequate parking spaces so that road bodies are used as an alternative to parking. Meanwhile, the Law of the Republic of Indonesia Number 22 of 2009 concerning Road Traffic and Transportation also stipulates that parking facilities can only be held in certain places which are declared by Traffic Signs and / or Road Markings. To prevent the rampant illegal parking violations, the Denpasar City Department of Transportation has taken orderliness. The aim is to determine the impact of orderliness parking and social behavior that can hinder and support the Denpasar City Department of Transportation in carrying out control of parking violations on road bodies. The writing method uses a descriptive method with a qualitative approach. The results show that the Denpasar City Department of Transportation in curbing illegal parking has a positive impact on restoring the function of urban space, see from several aspects that become benchmarks for implementation of orderliness among others standards and policy targets, resources, relationships between organizations, characteristics of implementing officers, social conditions, politics and economics, as well as the executing disposition. Changes in social behavior in the community are also needed to support illegal parking control, but several inhibiting factors from community behavior are still very much felt by the Denpasar City Transportation Agency in implementing parking control so that public awareness is needed. Changes in community behavior are the key to the successful impact of implementing illegal parking orderliness policies.